Optimization of a dry powder inhaler of ciprofloxacin-loaded polymeric nanomicelles by spray drying process. (28th May 2019) - Farhangi, Mahdieh; Mahboubi, Arash; Kobarfard, Farzad; Vatanara, Alireza; Mortazavi, Seyed Alireza
Abstract: Ciprofloxacin is a commonly prescribed antibiotic for treatment of pulmonary infections. Nanocarriers such as nanomicelles can increase the drug residence time in the lungs and enhance their antibacterial effects. Dry powder inhalers (DPIs) are the preferred pulmonary drug delivery system and preparation of an optimum nanoaggregate from nanomicelles by means of spray drying would be valuable. The two-level full factorial design was performed in 16 runs. The effects of carrier type, anti-adhesion agent type, carrier to nanoparticle ratio and anti-adhesion agent to carrier ratio on the size of the microparticles, their in vitro pulmonary deposition, and redispersibility were investigated. Its antibacterial effects against Pseudomonas aeruginosa, Klebsiella pneumoniae, and Streptococcus pneumoniae also were investigated. All independent variables were fitted into two-factorial interaction models. The optimum nanoaggregate was prepared using mannitol and L-phenylalanine with a D 0.5 of 1.7 µm and 60% fine particles. The process had no negative effect on the stability or drug release profile of the nanomicelles. The antibacterial effects of ciprofloxacin against microorganisms increased significantly. This spray drying process could be used for preparation of an optimum DPI from polymeric nanomicelles. This formulation could increase the efficacy of ciprofloxacin for treatment of pulmonary infections.